Aneurysm growth after brain tumor removal: case report - Prandini Mirto N.; Lacanna Santino N.; Tella Oswaldo I.; Bonatelli Antônio P. F. (Arquivos de Neuro-Psiquiatria)
A rare case of rapid growth of an aneurysm after a posterior fossa meningioma removal in a 69-year-old lady is reported. Serial angiography, cerebral computed tomography and magnetic resonance imaging are presented. The patient harbored risk factors to both aneurysm formation and growth as current cigarette smoking, arterial hypertension, female sex and reduction of intracranial hypertension. One-year follow up after the first surgical procedure is presented.